2020
DOI: 10.1097/dbp.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a Child with Phenylketonuria: Parental Experiences from a Eurasian Country

Abstract: Objectives: Phenylketonuria (PKU) and mild hyperphenylalaninemia (HPA) are characterized by increased blood phenylalanine concentrations varying from mild to severe. Management of PKU was reported to be time consuming and burdensome for caregivers. This study intended to explore the experiences of families caring for a child with PKU/HPA in a country with a high PKU rate. The aim of this study was to compare parental well-being between parents of children with and without dietary restrictions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…[ 36 ] In a study conducted in our clinic, it was observed that families had difficulties in terms of diet between healthy siblings and children with phenylketonuria. [ 37 ] In a study by Alaei et al, average phenylalanine levels and some factors affecting social status were compared. No relationship was found in terms of family size.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] In a study conducted in our clinic, it was observed that families had difficulties in terms of diet between healthy siblings and children with phenylketonuria. [ 37 ] In a study by Alaei et al, average phenylalanine levels and some factors affecting social status were compared. No relationship was found in terms of family size.…”
Section: Discussionmentioning
confidence: 99%
“…However, in line with prior research, a clear relationship between educational level and professional activity is evident. Nonetheless, Zengin Akkus discovered that depressive symptom scores in parents caring for children with PKU were linked to independent factors such as household income and perceived social support [ 59 ]. Similar impacts of income were reported in the study conducted by Abdelaziz [ 60 ].…”
Section: Discussionmentioning
confidence: 99%